Pengaruh Kepemimpinan dan Disiplin Kerja terhadap Kinerja Karyawan PT Berkah Rafasa Jaya - Putri, Tasya Dwi Tami; Iskandar, Iskandar (Jurnal EMT KITA, 2026)
This study aims to analyze the effect of leadership and work discipline on employee performance. The research employs a quantitative approach using a causal associative method. The population of this study consists of all employees at the research object, with the sample size determined based on the applicable sampling technique. Data were collected through the distribution of questionnaires using a Likert scale. The collected data were analyzed using multiple linear regression analysis with the assistance of SPSS software, including validity testing, reliability testing, classical assumption tests, t-test, F-test, and coefficient of determination (R²). The results of the study indicate that partially, leadership has a positive and significant effect on employee performance. In addition, work discipline also has a positive and significant effect on employee performance. Simultaneously, leadership and work discipline have a significant effect on employee performance. The coefficient of determination (R²) shows that leadership and work discipline are able to explain a portion of the variation in employee performance, while the remaining variation is influenced by other factors outside this study. Therefore, improving effective leadership and consistently implementing work discipline are expected to enhance employee performance optimally and sustainably.